The Role Of Empowerment Strategy In Organizational Crisis Management A Field Study On Urban Organizing Department In Lattakia City Council - Zaher, Bassam; Hallaj, Yasmin Adnan (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This study aims to study the relationship between the strategy of empowerment through its dimensions (the ability to initiate and behave appropriately, the freedom of workers to act, teamwork) and the management of the random housing crisis in the Urban Organizing Department in Lattakia City Council. The research concluded that the Urban Organizing Department is less interested in the ability to initiate and behave appropriately, and its interest in the existence of teams working to solve the problem of random housing crisis, and by relying on Pearson correlation coefficient, and regression analysis And the analysis of variance using SPSS25, a relationship was reached between the freedom of workers to manage and management of the random housing crisis. هدف هذا البحث إلى دراسة العلاقة بين استراتيجية التمكين من خلال أبعاده (القدرة على المبادرة والتصرف المناسب، حرية العاملين في التصرف، العمل الجماعي) وإدارة أزمة السكن العشوائي في دائرة التنظيم العمراني في مجلس مدينة اللاذقية حيث تم توزيع استبانة على العاملين في دائرة التنظيم العمراني في مجلس مدينة اللاذقية وبلغ عددهم 33 موظف، وخلص البحث إلى انخفاض اهتمام دائرة التنظيم العمراني بالقدرة على المبادرة والتصرف المناسب، واهتمامها بوجود فرق عمل تعمل على حل مشكلة أزمة السكن العشوائي، ومن خلال الاعتماد على معامل الارتباط بيرسون، وتحليل الانحدار البسيط، وتحليل التباين باستخدام برنامج spss25, تم التوصل إلى وجود علاقة بين حرية العاملين في التصرف وإدارة أزمة السكن العشوائي.